A new MCDM approach for ranking of candidates in voting systems. (4th June 2019) - Azadfallah, Mohammad
There is no doubt that the voting system is a powerful method to determine the winner of elections. Despite its usefulness, voting systems has some notable limitations. A significant drawback with this approach is that it's assumed there is no preference among voters. On the other side, voting systems is believed that to be a multi-criteria decision-making (MCDM) problem. In this paper, to resolve this limit, a new MCDM approach is proposed. In the proposed method [based on the improved analytic hierarchy process (AHP) model proposed by Asgharpour (2003)], it is assumed that the voters are not equally important. In continuation, for assigning different importance weights to voters, the voters are classified categories with different importance level. Therefore, the group with higher importance level may have a greatest effect and vice-versa. A comparative analysis is performed, and the proposed method seems to be more satisfactory than the conventional model (i.e., ranks mean, Borda, Copeland and the improved AHP model) for solving voting systems problems. In general, this paper suggests a framework for reducing the wrong suited candidates risks associated with voting systems.